Leading Organizational Well-being: A Challenge in Current Educational Contexts - Cerdas Montano, Virginia; Rosabal Vitoria , Satya; Monge Rodríguez, Ingrid (Innovaciones Educativas, 2025)
Educational organizations are characterized by their dynamic and changing nature, where multiple factors converge that affect the management of organizational well-being. In this regard, the current Costa Rican context presents challenges and opportunities for managers of educational centers, who are immersed in a multi-level structure that increases the complexity of addressing it. Therefore, for this immersion into the context, a descriptive qualitative approach was adopted aimed at analyzing the leadership of school principals related to the management of organizational well-being for the promotion of healthy environments. The participant population consists of 52 principals, 30 teachers, and 3 supervisors. As specific objectives, a description of the current context of educational centers regarding organizational well-being from the teaching, management, and supervisory perspectives is proposed, in addition to identifying challenges that educational centers face in managing organizational well-being and promoting healthy environments. Finally, the goal is to determine the role of school principals' leadership in managing organizational well-being and healthy environments in educational centers. Among the main conclusions, it is identified that the management of organizational well-being in educational contexts is configured as a strategic dimension that must be addressed as a priority by educational leaders. Likewise, multiple factors—including workload, family circumstances, and budget cuts—were found to directly impact both organizational well-being and the achievement of goals.